STRATEGIC ADVANTAGES OF MICROSOFT OFFICE 365, SHAREPOINT AND POWER PLATFORM IN CORPORATE INFORMATION SYSTEMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the strategic benefits of implementing Microsoft Office 365, SharePoint and Microsoft Power Platform in Enterprise Information Systems (EIS). Based on a review of official Microsoft documentation and research literature on strategic IT alignment and dynamic capabilities, it is shown how the listed platforms improve operational efficiency, accelerate digital transformation, ensure security and reduce the total cost of ownership. Arguments are made about the synergistic effect of an integrated ecosystem (Microsoft products) in achieving organizational goals.